Species composition, abundance and distribution of trees in a 4.3-hectar plot adjacent to the Mat-y gate of the University of the Philippines Visayas main campus, Miagao, Iloilo - Alaban, Annaveve Rose Miole
A 4.3-hectare plot across the UPV tennis court extending to the Mat-y gate of the campus was the area of study. The local names of each tree were identified. the girth-at-breast-height (GBH) and approximate height of trees were also recorded. From the data gathered, the Basal Area, Index of Dominance and Index of Diversity were computed., One thousand one hundred forty-five trees were found in the 4.3-hectare plot comprised of fifteen species of trees commonly known as "Eucalyptus", "Acacia", "Kamonsil", "Narra", "Mahogany", "Agho", "Apyan", "Gmelina", "Ipil-ipil", "Bugto-tae", "Lamnog"' and "Tabong". The value of the Index of Dominance is higher compared to the value of the Index of Diversity, which means that a species is exerting greater influence compared to other species. Eucalyptus is the most dominant tree species in the area of the study which is 75.63 percent of the whole population. The distribution of trees in the 4.3 hectare plot is not random and is mainly influenced by human intervention since it is a secondary forest.